Exploring maximizing, satisficing and minimizing tendency in decision-making among autistic and neurotypical individuals. (April 2022) - Rogge, Nicky
Highlights: Measure 6 types of decision-making tendency among ASD individuals and neurotypicals. Use of Decision Making Tendency Inventory measurement scale. Performs multi-group confirmatory factor analysis and comparison of latent means. Individuals with ASD are similar to neurotypicals in satisficing and minimizing. Individuals with ASD have higher tendency to maximize than neurotypicals. Abstract: Background: The tendency to maximize is one of the most frequently studied personal traits in choice-making and decision-making. In spite of the large resemblances between the decision behaviour that is characteristic for maximizers and the decision behaviour displayed by individuals with autism, and the considerable overlap in the list of decision problems and decision experiences commonly reported by maximizers and individuals with autism, the question whether individuals with autism are more maximizing in decision-making as compared to neurotypical controls, has remained unexamined in the literature. The paper measures and compares the tendency to maximize, satisfice, and minimize in choice- and decision-making among autistic individuals and age, gender- and education degree-matched neurotypical individuals. Method: The Decision Making Tendency Inventory measurement scale (Misuraca et al., 2015) is used to measure six types of decision-making tendency: fearful maximizing, resolute maximizing, more ambitious satisficing, less ambitious satisficing, parsimonious minimizing, and indolent minimizing. A multi-group confirmatory factor analysis and comparison of the differences in latent means is performed. Results: The results demonstrate that autistic individuals are similar to neurotypical individuals when it comes to having a tendency to satisfice or minimize in decision-making, however, autistic individuals do score higher in terms of adopting a fearful and resolute maximizing tendency than neurotypical individuals. Conclusions: Results suggest that higher maximizing tendency may explain for some of the difficulties experienced by autistic individuals in decision-making